Conventional and genetic risk factors for chronic Hepatitis B virus infection in a community-based study of 0.5 million Chinese adults - Elizabeth Hamilton; Ling Yang; Alexander J. Mentzer; Yu Guo; Yiping Chen; Jun Lv; Robert Fletcher; Neil Wright; Kuang Lin; Robin Walters; Christiana Kartsonaki; Yingcai Yang; et al. (Scientific Reports, 2022)
Abstract Despite universal vaccination of newborns, the prevalence of chronic hepatitis virus B (HBV) infection and the associated disease burden remain high among adults in China. We investigated risk factors for chronic HBV infection in a community-based study of 512,726 individuals aged 30–79 years recruited from ten diverse areas during 2004–2008. Multivariable logistic regression was used to estimate odds ratios (ORs) of hepatitis B surface antigen (HBsAg) positivity recorded at baseline by sociodemographic and lifestyle factors, and medical history. In a random subset (n = 69,898) we further assessed the association of 18 single nucleotide polymorphisms (SNPs) previously shown to be associated with HBsAg positivity and development of chronic liver disease (CLD) (1600 cases). Several factors showed strong associations with HBsAg positivity, particularly younger age (< 40 vs. ≥ 60 years: OR 1.48, 95% CI 1.32–1.66), male sex (1.40, 1.34–1.46) and urban residency (1.55, 1.47–1.62). Of the 18 SNPs selected, 17 were associated with HBsAg positivity, and 14 with CLD, with SNPs near HLA-DPB1 were most strongly associated with both outcomes. In Chinese adults a range of genetic and non-genetic factors were associated with chronic HBV infection and CLD, which can inform targeted screening to help prevent disease progression.